Autonomous multi satellites assembly in keplerian orbits - Okasha, Mohamed Elsayed Aly Abd Elaziz; Park, Chandeok; Park, Sang-Young (American Institute of Aeronautics and Astronautics, 2013)
In this paper, the guidance and control algorithms of an autonomous multiple satellite assembly are developed in a general keplerian orbit. The guidance algorithms are based on defining the velocity profile of each satellite in two different segment of space. In the first segment, the guidance law utilizes the analytical closed form solution of the satellite relative motion in close proximity in which the gravitational forces are considered. To avoid the singularity associated with the analytical solution, switching to the second segment of space is introduced to redefine the velocity profile as a function of the relative distance between satellites and relative distance to the desired goal location in the assembly. The guidance algorithms suggest attraction and repulsion forces between the individuals in which the attraction forces dominate on large distances while repulsion forces dominate on close distances. The Proportional-Derivative (PD) continuous feedback control and the velocity change Δv control algorithms are presented to perform efficient fuel consumption maneuver, while avoiding collisions and to track the guidance trajectories. Numerical simulations are performed to assess the precision of these algorithms in hexagonal and cubic formation assembly.